Joyful Learning: Alternative Learning Models to Improving Student’s Happiness - Caraka Putra Bhakti; Muhammad Alfarizqi Nizamuddin Ghiffari; Khansa Salsabil (Jurnal VARIDIKA, 2018)
The purpose of this paper to explain the happiness learning model indeveloping student’s potential. Every human being has the potential in their self. the potential of the human being developed through an optimal education. Currently, the applied education focuses more on student learning or student center. Implementation of student center learning will right facilitate students in learning. This is because the student center learning in accordance with the needs of students and focuses on the students themselves. However, in the learning process of the student is not just learning ordinary or just formality, but need psychological attention from the students themselves. During the learning process, students also need to feel excited and happy to learn something. Happiness learning is learning to build a mentally healthy, pleasant surroundings and so forth. Thus, students are not only focused on the subject matter but also enjoy and interpret the lessons learned. Appropriate learning model will be able to realize a happiness learning. We recommend Joyful learning, which is an alternative learning that is not just learning in general, but also focusing on the student, and able tocreate meaning in learning. Joyful learning was doing with several stages, starting from creating a pleasant environment until mean in learning. In joyful learning, the teacher is important to create a positive environment, which is supported by effective learning media in the form of pictures or videos that applied learning more fun. From happiness learning model will be able to enhance human potential optimally.